Problems and issues of the Russian insurance market in conjunction with reinsurance and economic security - L. A. Akhmetov (Путеводитель предпринимателя, 2020)
The article considers the problems and issues of the insurance market of Russia in relation with reinsurance as one of the most significant factors of economic security. Successful formation of the insurance market hinders its criminalization, representing a direct threat to the economic security of the state and subjects of economic relations in this sphere. Study on the possible forms and methods of participation of the bodies of internal Affairs in providing of economic safety in the reinsurance sphere is extremely urgent and necessary from a practical point of view.